Optimización de parámetros tecnológicos para la elaboración de bebida instantánea liofilizada (Panetela) a base de plátano verde (Musa paradisiaca L.) y leche - Waldo Saldaña, Susana del Pilar (2015)
The. deve!opment of this currcnt ínvesti~1ation requests conducting evaluations and techno!ogical parameters controls during the elaboirat1on of the drink as well as physical, chemicaI analyzes on raw materials _as well as microbiological analyzes and evaluation of final product quality attributes. Because of the large production :>f banana in the San and the large daily consumption of this product, we saw the necessity to increase the shelf life and nutritional value of this food, elaborating an instant and enriched drink with sugar and fresh milk, seeking to improve the feGding of the population, at the same time, increasing demand of this agroindustrial farming, and €~ncouraging grow of banana plant to improve the economic incomes of of the majority of farmers dedicated to this crop. This instant drink is an mixture 1~; a mixture which when reconstituted by simple dilution in bni~ed water is able to solubilize c.nd swel! increasing its volume and fOíming a viscous solution irr.mediately without any lurnps. To prepare instant drink was obta1ned by the flow chart: Banana green ---. selection and dassification --• washed and peeled--+ cut ----. liquid and mix of ---+ cooking ---.. cast 1 --• cooled -~rozen ·---.lyophilized ---• crushed ---. cast 2 -~·+ pacl<ing and sealing __ ...,.. stored. Obtainir.g the. instantbeverage is made using the lyophilization process optimized with the following pararneters .T°cong =-?O ºC, P = 0.045 mbar, Tºliof = -80 º.C, tliof = 20 h, because it is good for the dehydrated and COQservation,pf products considéred as the best method of dehydration to preserve the organoleptic and nutritional characteristics of the food, giving them added value .. In this process of drying the product obtained is not altered in its properties and is easily rehydrated. To produce this type of product. the optim~I rnix of ingredients was deve!oped with the foiiowing rates: 13.53% of mass of green banana, sugar 18.15%, 54.66% of fresh milk and 13.66 <>ó water, proper proportions that lead to ideal formula of the drink . For a complete drink for safe cor:sumption, the fo!lowing analy~is of the lyophilized product is made: physic - chemicai yleld moL:;ture